Synthesis, conformational study and antiviral activity of l-like neplanocin derivatives. Issue 18 (15th September 2017) - Chen, Qi; Davidson, Amber
Graphical abstract: Abstract: Thel -like enantiomer of 9-(trans-2′, trans-3′-dihydroxycyclopent-4′-enyl)-3-deazaadenine (DHCDA) (1 ), its 3-deaza-3-bromo derivative (3 ), and the conformational restricted methanocarba (MC) nucleoside analogues (2 and4 ) were synthesized. X-ray crystal structures showed the L isomer MC analogue4 adopts a similar North-like locked conformation as conventional D-MC nucleosides, while the DHCDA analogue3 preferred south-like conformer. Compounds1 and4 showed potent antiviral activity against norovirus, while compound2 and3 were less potent or inactive. The conformational behavior of "sugar" puckering (north/south) and nucleobase orientation (syn /anti) may contribute to the antiviral activity differences. For compound3, antiviral activity was also found against Ebola virus.